Experimental study on axial compressive behavior of rubberized interlocking masonry walls - Al-Fakih, A. (Elsevier Ltd, 2020)
The behavior of rubberized interlocking masonry walls is substantially influenced by the properties of the waste materials used, which makes them behave differently from conventional interlocking masonry systems. Ten each of hollow and grouted walls were constructed using rubberized interlocking bricks and then tested under compressive loading. Rubberized interlocking bricks are made using 10 crumb rubber and 56 fly ash as a partial replacement for fine aggregates and cement by volume, respectively. The structural behavior, including strength, load-deformation performance, stress-strain relations, and failure mechanisms of the tested load-bearing walls have been investigated. The results reveal the ability of rubberized interlocking masonry walls to withstand axial compressive of 3.87 MPa for hollow and 5.75 MPa for grouted specimens, which is approximately 15â20 lower than in conventional interlocking masonry walls. Web splitting, vertical cracking and face spalling were common failure modes for hollow and grouted rubberized interlocking masonry walls. In contrast to conventional interlocking walls under compressive loading, rubberized interlocking walls show increased ductility and undergo measurable post-failure loads with significant displacement due to the presence of crumb rubber, which permits a large expansion of microcracks inside the specimens after failure. Rubberized interlocking walls also tend to have large initial deflections as the bricks settle and the gaps caused by dry joints close. Â© 2019 Elsevier Ltd